CHALLENGES, IMPLICATIONS AND ETHICAL FRAMEWORK RELATED TO ARTIFICIAL INTELLIGENCE IN HEALTH: TOWARDS AN ETHICAL ARTIFICIAL INTELLIGENCE FOR MEDICINE - DUGUET, Julien; CHASSANG, Gauthier; BÉRANGER, Jérôme (MEDECINE LEGALE DROIT MEDICAL, 2025)
A climate rotating hot and cold has developed, alternating between enthusiasm and suspicion towards digital technology, and the developments of Artificial Intelligence (AI). This results in a more fragile relationship of trust between professional particularly in the health sector and citizens. Faced with growing challenges surrounding AI in medicine, an ethical vision is necessary to find coherence and meaning in the approach of this new technology. This ethical reflection refers to an ethical system of values that are associated with four universal ethical principles especially in biomedical: people’s autonomy, beneficence, non-maleficence and justice. Therefore, intelligent machines must be ethical from their design to their use. Responsibility attached to the machine lies with both designers and owners. Thus, it is essential to bring “legal identity” to these AIs through an algorithmic ethical consciousness. Ultimately, the notion of responsibility must be at the heart of the doctor-AI-patient relationship.